Perception and acceptance of micronutrient-Fortified Bouillon among Non-Index Household Members: A longitudinal sub-study nested within a randomized trial in Northern Ghana - Felix Kwaku Kyereh; Agartha N. Ohemeng; Reina Engle-Stone; K. Ryan Wessells; Sika M. Kumordzie; Charles D. Arnold; Jennie N. Davis; Emily R. Becher; Ahmed D. Fuseini; Kania W. Nyaaba; Xiuping Tan; Stephen A. Vosti; et al. (PLoS ONE, 2026)
Background Fortified bouillon cubes offer a scalable strategy to address micronutrient deficiencies in West Africa. However, success depends on household members’ perceptions and acceptance. This study assessed changes in perception and acceptance of fortified bouillon cubes over time and explored factors influencing these outcomes among non-index household members (NIHMs) from trial households in Northern Ghana. Methods This longitudinal mixed-methods study was nested within a double-masked randomised controlled trial. Households received micronutrient-fortified bouillon cubes (vitamin A, vitamin B12, folic acid, iron, zinc, iodine) or control cubes (iodine only) for nine months. One NIHM (≥15 years) per household (n = 1,047) was enrolled. Structured interviews were conducted during early (months 1–2; n = 731) and late (months 7–9; n = 796) phases. Composite perception (8 items) and acceptance (10 items) scores (range: 1–5; higher scores = more positive perceptions/greater acceptance) were derived from an 18-item validated instrument. Bayesian linear mixed-effects models assessed temporal changes and associated individual and household factors. Twenty-four focus group discussions (months 4–5) explored drivers and barriers. Results Mean age of NIHMs was 40 ± 14.7 years; 59% were female. Perception scores increased over seven months, from 3.4 to 4.1 (adjusted posterior mean difference [aPMD] = 0.69; 95% credible interval [CrI]: 0.57, 0.81). Acceptance remained high (4.59 to 4.58; aPMD = –0.02; 95% CrI: –0.07, 0.03). No differences were observed between trial arms. At early timepoint, perception scores were lower among household heads compared with other household members, and lower among formal employees compared with farmers. Acceptance was higher among individuals from severely food-insecure households and lower among those from mildly food-insecure households. Focus groups revealed that perceived health benefits, sensory appeal, and cultural fit drove acceptance, while infertility-related myths and food colour changes were barriers. Conclusion Fortified bouillon cubes were accepted, with perceptions improving over time. Public education will be essential to address misconceptions. Trial registration ClinicalTrials.gov ( NCT05178407 ); Pan-African Clinical Trial Registry (PACTR202206868437931). The authors confirm that all ongoing and related trials for this intervention are registered.